Binding earth and heaven : patriarchal blessings in the prophetic development of early Mormonism - Shepherd, Gary, 1943-; Shepherd, Gordon, 1943- (The Pennsylvania State University Press, 2012)
Focuses on Mormonism as a case study of how unpopular new religions may survive and even flourish in spite of unrelenting opposition. Examines early patriarchal blessings bestowed upon early converts to Mormonism from 1834-1845, and their function as a commitment mechanism for converts.